2013 46th Hawaii International Conference on System Sciences 2013
DOI: 10.1109/hicss.2013.398
|View full text |Cite
|
Sign up to set email alerts
|

Media Watch on Climate Change -- Visual Analytics for Aggregating and Managing Environmental Knowledge from Online Sources

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…For example, researchers have shown that the public can generate and spread information during natural disasters and other emergencies using social media outlets, such as Twitter [4]. It is also possible to gauge disease activity [5] and public sentiment on climate change [6]. While Twitter provides an endless stream of conversations for potential study, making sense of and drawing conclusions from such large data sources is challenging.…”
Section: Justification For Visual Analytics and Twitter Usementioning
confidence: 99%
“…For example, researchers have shown that the public can generate and spread information during natural disasters and other emergencies using social media outlets, such as Twitter [4]. It is also possible to gauge disease activity [5] and public sentiment on climate change [6]. While Twitter provides an endless stream of conversations for potential study, making sense of and drawing conclusions from such large data sources is challenging.…”
Section: Justification For Visual Analytics and Twitter Usementioning
confidence: 99%
“…Media frames of climate change have typically been studied by analysing highquality newspapers worldwide (e.g., Akerlof et al, 2012;Dotson et al, 2012;Nerlich et al, 2012;Vestergård, 2011;Zamith et al, 2013) and to some extent tabloids (e.g., Kumpu, 2013;Waitt et al, 2012) and on-line sources (e.g., Jančevskaite and Telešiene, 2013;Scharl et al, 2013;Thorsen, 2013). In an analysis of United States (US) media and political debate from the late 1990s and onwards, Nisbet and Scheufele (2009) (Boykoff, 2008), describing climate change as sensational, alarming (Hibberd and Nguyen, 2013;Russill and Nyssa, 2009), and harmful (Ambler, 2007;Carvalho and Burgess, 2005;Zamith et al, 2013).…”
Section: Media Frames Of Climate Changementioning
confidence: 99%
“…Figure 1 shows a screenshot of the Media Watch on Climate Change [1], a news and social media aggregator available at www.ecoresearch.net/climate. Within the DecarboNet research project (www.decarbonet.eu), this publicly available platform is currently extended into a collective awareness platform, in close collaboration with NOAA Climate Program Office (www.climate.gov) and the World Wide Fund for Nature (www.wwf.ch).…”
Section: Introductionmentioning
confidence: 99%